Do acesso à calçada ao acesso à cidade: acessibilidade na mobilidade urbana em Ituiutaba-MG - Silva, Daniel de Araújo (2017)
The issue of urban accessibility is important to society as a whole at a time when a significant portion of cities yearn for the right to the environment. From this perspective, we share the idea that mobility and urban accessibility are basic conditions for every citizen to travel around the city, both for people with some kind of disability, reduced mobility, elderly and pregnant, as well as for those who travel without any difficulty. Therefore, the main objective of this research was to analyze the accessibility in urban mobility in Ituiutaba - MG. We work with the perspective of contemplating more specific and complementary objectives, such as: a) Analysis of public roads (streets and sidewalks) focusing on the safety and comfort of the pedestrian; B) Evaluation of accessibility instruments; C) Research on the situation of urban collective public transportation with regard to accessibility; D) Analysis of how access is given to commercial establishments, public agencies and squares; E) Diagnosis of the mobility and accessibility conditions, carrying out evaluations in places of the central area and beyond. In order to comply with the purposes and perspectives of the research, we adopted some methodological procedures in search of the results. With regard to the theoretical-conceptual bias, we carried out a bibliographical research, based mainly on the concepts related to urban mobility, accessibility, urban space and universal design, among others, with the objective of obtaining a theoretical basis, aiming at the necessary foundation for a better application on the fieldwork, as well as the articulation between theory and empiricism.In relation to the fieldwork, we used the method of direct observation to the research object, that is, each element that we investigated, we visited the place, recorded the characteristics, performed the photographic record, analyzed the data collected and compared if the elements are in accordance with current laws and regulations, in addition to cartographic treatment. In this way, we analyzed the center of the city and the areas beyond it, such as the movement of a pedestrian from when he leaves his residence up to his destination, based on the following aspects: accessibility on the sidewalk; Intersections and crossings; Access to commercial establishments and public agencies, accessibility tools in public areas; And accessibility in public transportation. The results indicate that the city of Ituiutaba does not offer an accessibility structure for its citizens, even though there are some sites with some instruments, but they do not meet the specifications of the ABNT NBR 9050 (2015) standard. We also note that the situation in the neighborhoods is worrying, since the equipment and locations are infrequent and / or nonexistent. Therefore, through the analysis and reflection proposed here through the research, we consider that the city of Ituiutaba, taking as reference the space cuts does not offer accessibility to all people in a universal way, since the instruments of accessibility are not present in Effective way: on sidewalks, crossings and intersections, in commercial establishments and municipal agencies, public transportation and in the squares. These instruments are primordial and basic in order to guarantee the right to the environment and the right to the city, either as a whole or to its parts. In addition, more effective urban planning, together with an urban mobility plan, is required to meet the requirements of people moving around and around the city as a whole, such as comfort, security and independence, ie accessibility. Only in this way, the citizen can effectively have guaranteed his right to the city.